CHAMOMILE FLOWER EXTRACT AS NATURAL DIETARY GROWTH PROMOTER AND ANTIOXIDANT FOR BROILER CHICKENS - Gamal A. A. Hamady; Mamdouh A. Abdel-Moneim; Mohamed A. El-Sherbiny; AhmedM. El- Shinnawy; Hady F.A. Motawe; Ghadir A. El-Chaghaby (Journal of Animal and Plant Sciences, 2017)
The present study was conducted to investigate the effect of dietary supplementation of chamomile flower extract (CFE) on broilers’ performance, carcass traits and meat quality under refrigerated storage conditions. In vitro examination has proved that CFE had growth-inhibiting effect on certain Gram positive and Gram negative bacteria. In the growth trial, three corn-soybean meal-based diets (starter, grower and finisher) were formulated and fed to the control group of broiler chickens during the age intervals of 1-14, 14-28 and 28- 42 days, respectively. A second group of birds was fed on the same three diets supplemented with 75 ppm CFE. The results showed that body weight gain of birds fed the CFE-supplemented diet was significantly higher (2365.33 gm) compared to the control group (2199.00 gm). Also, feed intake and dressing weight were positively affected as a result of feeding the CFE-supplemented diet but feed conversion ratio was not affected. The estimated value of European production efficiency factor for the tested extract was higher than that of the control group. The percentage of (DPPH) scavenging activity in meat of broilers fed the CFE-supplemented diet was a higher significantly (48.33-45.67-39.00 %) compared to the control group (38.67-35.00-19.33 %) at 1- 4 -7 days of refrigerated storage) respectively. While the TBARS values were lower significantly (0.400-0.427-0.530 mg) compared to the control group (0.483-0.610-0.760 mg) at 1- 4 -7 days of refrigerated storage) respectively. It is concluded that added dietary CFE has a positive effect on broilers’ performance and can act as a potent preservative of refrigerated chicken meat; thus, dietary addition of CFE can prolong the shelf life of meat.
Keywords: Chamomile flower; performance; antibacterial; antioxidant; meat quality; broilers